2017
DOI: 10.11622/smedj.2016047
|View full text |Cite
|
Sign up to set email alerts
|

Relapsing polychondritis in Singapore: a case series and review of literature

Abstract: INTRODUCTIONRelapsing polychondritis (RP) is a rare immune-mediated condition, which is characterised by recurrent and progressive inflammation of cartilaginous structures and proteoglycan-rich structures.(1) RP particularly affects the cartilaginous areas of the ears and nose, and it is not uncommon for the eyes, joints and respiratory tract to be affected as well. RP can occur in isolation or in association with other diseases. The objective of the present study was to describe the clinical presentation, tre… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
5
1

Year Published

2018
2018
2022
2022

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 11 publications
(6 citation statements)
references
References 20 publications
(7 reference statements)
0
5
1
Order By: Relevance
“…Elevated ESR and CRP may be detected during the acute onset of RP, but more than 10% of patients have a normal CRP level even during an RP flare [ 2 ]. In contrast to results from Chuah et al [ 28 ], who observed elevated ESR in 80% and CRP in 50% of their study, only 10% of cases from our study presented significantly increased levels of inflammatory markers.…”
Section: Discussioncontrasting
confidence: 99%
“…Elevated ESR and CRP may be detected during the acute onset of RP, but more than 10% of patients have a normal CRP level even during an RP flare [ 2 ]. In contrast to results from Chuah et al [ 28 ], who observed elevated ESR in 80% and CRP in 50% of their study, only 10% of cases from our study presented significantly increased levels of inflammatory markers.…”
Section: Discussioncontrasting
confidence: 99%
“…Previous reports have suggested that elderly patients with RP are at risk of MDS or hematological malignancy ( 12 ). Additionally, previous studies demonstrated the co-occurrence of RP or VEXAS syndrome and B-cell or plasma cell neoplasms, but these patients were not complicated with MDS ( Table 1 ) ( 1 , 5 , 13 16 ).…”
Section: Discussionmentioning
confidence: 99%
“…Scleritis/episcleritis is the most common ocular complication associated with RPC (Table 3) [10,[26][27][28][29][30][31][32][33][34]. Most cases of scleritis occur bilaterally.…”
Section: Scleramentioning
confidence: 99%
“…Lichauco et al reported a case of RPC with an orbital mass, and a biopsy of the orbital lesion showed mucosa-associated lymphoid tissue B-cell lymphoma [74]. In addition, a high incidence of hematological malignancies, including leukemia, multiple myeloma, and lymphoma, has been reported in RPC patients [28,[75][76][77]. Therefore, biopsy of the orbital mass should be considered when the effectiveness of corticosteroid treatment is insufficient.…”
Section: Orbit and Miscellaneousmentioning
confidence: 99%